039. Obstructive Ileus Caused by Colitis Tuberculosa: A Case Report - Kurniati, Rizki; Pustaka, I Gusti Ngurah (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical EducationDO - 10.24843/JBN.2024.v08.is02.p039, 2024)
Background : Gastrointestinal TB (GTB) constituting approximately 1% to 3% of all TB globally and characterized including of any part of digestive system and its related organs. Results : A 61 years old man was admitted to emergency departement with abdominal pain and abdominal distention since 6 months and getting worse in 1 day. He also complained dispneu. On examination, the abdomen was rigid, distended, and tender and the lung has wheezing. The radiographs of abdomen revelved dilated loops of the small intestine with multiple air-fluid levels suggestive of small intestine obstruction. A chest radiograph showed active TB with opacity of the right lung.  The patient was planned for exploratory laparotomy and founded anastomosis, peritoneal deposits, matted bowel, and a perforation of ileus. Intraoperative biopsy was taken from the ileus perforation and revelved tuberkulosa infected. Postoperatively, he was started antituberculous theraphy (ATT) of Rifampicin, isoniazid, and ethambutol (RHE). Conclusion: Obstructive Ileus is a complication of gastrointestinal tuberculosis in patients with a history of untreated latent tuberculosis.